A review of middleware approaches for energy management in distributed environments. (10th July 2012) - Noureddine, Adel; Rouvoy, Romain; Seinturier, Lionel
SUMMARY: Energy management solutions and approaches for computer systems are becoming broadly available as energy concerns are becoming mainstream. Many approaches have been proposed to manage the energy consumption of the hardware, operating system, or software layers. The widespread usage of ubiquitous devices and the high coverage of networks (Wi‐Fi and 3G) have led to a new generation of communicating and mobile devices that uses complex middleware platform functionalities. Therefore, energy management has emerged as a topic of research interest in the middleware layer, and solutions specific to this layer are proposed along the more traditional ones existing at the other levels. In this article, we report on a review of state‐of‐the‐art approaches for energy management middleware platforms. This article defines also an architectural taxonomy and compares existing approaches on the basis of this taxonomy. In particular, we review middleware platforms and detail a number of approaches where energy management is handled. Finally, we review application scenarios where the energy management concepts at the middleware layer are applied in intelligent environments. Copyright © 2012 John Wiley & Sons, Ltd.